2022
DOI: 10.18261/pof.38.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Ombruk av bygningsdeler – læringspunkter fra forbildeprosjekter i Norge, Danmark og Belgia

Abstract: Ombruk av bygningsdeler kan bidra til lavere utslipp og mindre avfall fra byggenaeringen. I denne artikkelen beskriver vi hva vi kan laere fra seks forbildeprosjekter i Norge, Danmark og Belgia. Rammevilkårene for ombruk varierer mellom landene, og vi vurderer prosjektene med hensyn på 1) type ombruk, 2) dokumentasjon og sertifisering, 3) juridiske og politiske rammevilkår, 4) kostnader og tidsbruk og 5) anskaffelse og avhending. Å sette konkrete ombruksmål er den viktigste suksessfaktoren som bør tas med i fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…From Sandberg E, Fufa S M, Knoth K and Eberhardt L C M [11], looking at projects in Belgium, Denmark, and Norway, it is found that established marketplaces and access to intermediate storage are key factors for realising reuse projects, and that digitalisation can be a good contributor. The findings from the study indicate the importance of calculating the actual achievements of the projects.…”
Section: International Trends/state Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…From Sandberg E, Fufa S M, Knoth K and Eberhardt L C M [11], looking at projects in Belgium, Denmark, and Norway, it is found that established marketplaces and access to intermediate storage are key factors for realising reuse projects, and that digitalisation can be a good contributor. The findings from the study indicate the importance of calculating the actual achievements of the projects.…”
Section: International Trends/state Of the Artmentioning
confidence: 99%
“…It is a need to systemize the logistics of reuse within the public sector, to be able to meet the need with what is available. Sandberg E, Fufa S M, Knoth K and Eberhardt L C M [11] emphasise the importance of performance indicators for a successful implementation of circular economy and the lack thereof in the municipalities might explain why the public sector in Norway is lagging compared to other countries.…”
Section: Measurements To Increase Reusementioning
confidence: 99%